Спектроскопія у зазорі: фаза відбитої хвилі і характеризація плівок - Turchin, A. V. (Publishing house "Academperiodika", 2018)
Optical methods that are used to characterize the state of a surface covered with films are based on the measurement of either the ratio between the complex reflection coefficients for mutually orthogonal light polarizations (ellipsometry) or the magnitudes of reflection coefficients themselves; afterward, the parameters of films such as their number, thicknesses, and transparencies can be determined by the fitting, while solving the corresponding inverse problem. In order to extend the set of quantities that can bemeasured experimentally, a method is proposed that allows the phase of the reflected light wave to be determined, by analyzing the spectral features for light reflected from a plane-parallel gap between the surface of analyzed specimen and the environment. In particular, the spectrum obtained, by using the “moving specimen” procedure, can be transformed into the spectral dependences of the magnitude and phase of the reflection coefficient. As a result, the inverse problem of finding the dielectric permittivity of a single-layer film is reduced to the solution of a linear matrix equation, which makes the proposed method more advantageous in comparison with the ellipsometric one, for which there is no direct relationships between the ellipsometric angles and the physical parameters of the film.